Synergistic Activation uponMETandALKCoamplification Sustains Targeted Therapy in Sarcomatoid Carcinoma, a Deadly Subtype of Lung Cancer. Issue 5 (May 2016) - Pelosi, Giuseppe; Gasparini, Patrizia; Conte, Davide; Fabbri, Alessandra; Perrone, Federica; Tamborini, Elena; Pupa, Serenella M.; Ciravolo, Valentina; Caserini, Roberto; Rossi, Giulio; Cavazza, Alberto; Papotti, Mauro; et al.
ABSTRACT : Introduction: : Genetic alterations suitable for targeted therapy are poorly known issues in pulmonary sarcomatoid carcinoma (PSC), an uncommon and life‐threatening family of non–small cell lung cancers. Methods: : Ninety‐eight PSCs were assessed for MNNG HOS Transforming gene ( MET ) and anaplastic lymphoma receptor tyrosine kinase gene ( ALK ) status by fluorescence in situ hybridization (FISH) and for relevant protein expression by immunohistochemical analysis, also taking advantage of phosphorylated (p‐) antibodies. Moreover, levels of ALK and MET mRNA were also determined by real‐time polymerase chain reaction and Western blot analysis for downstream activation pathways involving p‐MET, p–protein kinase B, p–mitogen‐activated protein kinase, p‐SRC proto‐oncogene tyrosine‐protein kinase, and p–focal adhesion kinase (p‐FAK). Results: : MET amplification was detected by FISH in 25 of 98 PSCs (25.6%) and ALK amplification (but not the relevant rearrangement) was found in 16 of 98 (16.3%), with all ALK ‐amplified tumors also showing MET amplification ( p < 0.0001). Nine PSCs, however, showed MET amplification without any ALK gene alteration. ALK protein expression was always lacking, whereas MET and p‐MET were confined to the relevant amplified tumors only. Increased levels of ALK and MET mRNA were detectable in tumors with no direct relationship between mRNA content, protein expression, or alterations detected by FISH. Western blot assays showed complete activation of downstream signal pathways up to p‐SRC proto‐oncogene tyrosine‐protein kinase, and p–focal adhesion kinase recruitment in MET and ALK– coamplified tumors only, whereas isolated MET amplification, MET and ALK borderline amplification (5% – 10% of tumor cells with ≥15 copies of the relevant gene), or negative tumors showing eusomy or chromosome polysomy were confined to p–mitogen‐activated protein kinase, p–protein kinase B, and/or p‐MET activation. Multivariate survival analysis pushed a higher percentage of MET altered cells or a higher value of MET copy gain per cell to marginally emerge for overall survival ( p = 0.140) and disease‐free survival ( p = 0.060), respectively. Conclusions: : ALK and MET seemed to act as synergistic, nonrandom coactivators of downstream signal when coamplified in a subset of patients with PSC, thus likely suggesting a combined mechanism of oncogene addiction. These alterations could be a suitable target for therapy based on specific inhibitors.